Práticas de estudos de alunos mediados pelo CD-ROM " Física Animada - Termodinâmica" no ensino médio - Gielton de Barros Lima (2004)
The purpose of this work is to investigate social practices of study experienced by a young man and womans group, when they develop activities which involves computational resources in which texts, images, sounds and movements are articulated. Thus, we follow a student group of private High School in Belo Horizonte, with different profiles, while they have been engaged in extra-class activities using a specific CD-ROM: Fisica Animada Termodinâmica. We investigate young men and women students with high access to symbolic goods in our society. They have, also, access to the material and social-cultural conditions to do their studies. They use, frequently, digital technologies, but in the moment that they are studying, they go over mainly the text book and notebook. Their experiences point out the evidence that they are in a moment of transition between the analogical and digital, between mass media communication and bidirectional transmission. The CD-ROM used as studies mediator was developed by me, a High School Systems Physics teacher. The CD was conceived as a material for supporting the students studies and is embodied by believes, values, conceptions about education, constructed in my professional life-time. This research is developed from the identification of some studys practices in the conditions showed above and analyzed through ideas that was developed by Vygotsky, Bakhtin, Gunter (and others), in the language field. From the datas analyzes, we identify that the majority of the students navigated the CD in a linear way, read the scream, waited for the construction of the screams e solved exercises reading the comments. When they made relationships with this kind of studies practice with their learning process, the students said that the text seems to be objective and understandably. The materials organization in topics, in the students opinion, made the access of the contents easier and the study more dynamic and practice. They said, also, that the orchestration communications modes conduits, in a certain way, the reasoning calling the attention to the important information in each moment. According to the students, the reading of the comments of the exercises provides a reflection about the problems, facilitating the comprehension, making clear the doubts arising during the exercises resolution and making the study more autonomous. This study pretend to clarify how this new field in the education history has to be investigated.